A Detailed View of 2‐Methylisoborneol Biosynthesis1. Issue 7 (11th January 2013) - Brock, Nelson L.; Ravella, Srinivasa R.; Schulz, Stefan; Dickschat, Jeroen S.
<x xml:space="preserve">Abstract</x> Odor of earth: Several homomonoterpenes were identified in actinomycetes that produce 2‐methylisoborneol (2‐MIB, see scheme, which is responsible for an earthy odor in drinking water). Their occurrence clarifies the 2‐MIB pathway, because they are derived from cationic intermediates that are otherwise difficult to detect. A highly sensitive method using feeding experiments with 13C‐labeled precursors gives detailed insights into 2‐MIB biosynthesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>